Mediation, schlichtung, verhandlungsmanagement : Formen konsensualer streitbeilegung - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2005)
English Abstract: The script deals with the procedures and legal basis for extrajudicial, consensual dispute resolution. The differences, special features and possible combinations of the different processes are presented in a clear form. The focus is on negotiation management and mediation. Current trends in mediation in Germany with a view to the Anglo-American "pioneering" countries are taken into account. German Abstract: Das Skript behandelt die Verfahren und rechtlichen Grundlagen der außergerichtlichen, konsensualen Streitbeilegung. In übersichtlicher Form werden die Unterschiede, Besonderheiten und Kombinationsmöglichkeiten der unterschiedlichen Verfahren dargestellt. Im Mittelpunkt stehen Verhandlungsmanagement und Mediation. Aktuelle Entwicklungstendenzen der Mediation in Deutschland mit Blick auf die angloamerikanischen "Vorreiter-" Länder werden berücksichtigt.